Application of whole exome sequencing in elucidating the phenotype and genotype spectrum of junctional epidermolysis bullosa: A preliminary experience of a tertiary care centre in India. Issue 1 (April 2017) - Yenamandra, Vamsi K; Vellarikkal, Shamsudheen K; Kumar, Manoj; Chowdhury, Madhumita R; Jayarajan, Rijith; Verma, Ankit; Scaria, Vinod; Sivasubbu, Sridhar; Ray, Subrata B.; Dinda, Amit K; Kabra, Madhulika; Kaur, Punit; et al.
Highlights: Junctional epidermolysis bullosa (JEB) is a clinically and genetically heterogenous group of genetic skin disorders. We show the utility of WES in understanding the phenotype and genotype spectrum in four Indian JEB families. Computational modeling studies have been used to understand the probable molecular consequence of a missense mutation on the structure-function relationship of lamininβ3 protein. This is the first report documenting the phenotype-genotype correlations of JEB patients from India. Abstract: Background: Junctional epidermolysis bullosa (JEB) is a diverse group of genodermatoses associated with extreme skin fragility. Despite several well-characterized genetic studies, molecular diagnosis of this heterogeneous group is still challenging. Recent advances in the field of genomics have seen the successful implementation of whole exome sequencing (WES) as a fast and efficient diagnostic strategy in several genodermatoses. Objective: In view of the scarcity and need of molecular studies for JEB in India, we sought to explore the potential of WES in understanding the mutational spectrum of this rare, in certain subtypes lethal, sub-group of EB. Methods: WES was performed using genomic DNA from each case of EB, followed by massively parallel sequencing. Resulting reads were mapped to the human reference genome hg19. Sanger sequencing subsequently confirmed the potentially pathogenic mutations. Results: Overall, four unrelated families (6 patients) of JEB with a highly variable clinical presentation including a rare case of LOC syndrome were studied. WES revealed 4 variations in 3 genes ( LAMA3, LAMB3 and COL17A1 ) that are implicated in JEB. None of the variations were recurrent. In addition we proposed the probable molecular consequence of a missense mutation on the structure-function relationship of lamininβ3 protein through computational modeling studies. Conclusions: Being the first report documenting the phenotype-genotype correlations of JEB patients from India, our preliminary experience with WES is clearly encouraging and serves as a nidus for future large-scale molecular studies to actively identify and understand JEB patients in Indian population.